Continental Survey of Access to Diagnostic Tools and Endovascular Management of Aneurysmal Subarachnoid Hemorrhage in Africa - Dokponou, Yao Christian Hugues; Kotecha, Jay; Bandyopadhyay, Soham; Erhabor, Joshua; Ooi, Setthasorn Zhi Yang; Egiz, Abdullah; Boutarbouch, Mahjouba; Dalle, David Ulrich; Higginbotham, George; Thioub, Mbaye; Sichimba, Dawin; Bankole, Nourou Dine Adeniran; et al. (Frontiers in Surgery, 2021)
Abstract Rationale: Interventional neurovascular procedures are effective in lowering the burden of aneurysmal subarachnoid hemorrhage (aSAH). Despite the wide uptake of interventional neurovascular procedures in high-income countries, access to care in low- and middle-income countries remains limited, and little is known about accessibility in Africa. In this survey, we decided to assess access to diagnostic tools and treatment of aSAH in Africa. Methodology: A Google form e-survey was distributed to African neurosurgery canters accepting responses from 4th January to 21st March 2021. Data on accessibility to diagnostic tools, treatment methodologies, and interventional neuroradiology personnel in African centers were collected. 95% confidence intervals were computed for each variable. Results: Data was received from 36 neurosurgical centers in 16 African countries (16/54, 30%). Most centres were public institutions (67%, 95% CI=52-82%). 94% (95% CI =86-100%) of the centers had the necessary resources for a lumbar puncture (LP) and a laboratory for the diagnosis of aSAH. Most centres (83%, 95% CI=71-95%) had at least one computed tomography (CT) scanner, 81% (95% CI=68-94%) of the centres had access to CT angiography and some had access to conventional angiography (47%, 95% CI=31-63%). 47% (95% CI=31-63%) of the centers could obtain a head CT within 2 hours of presentation in an emergency. 61% (95% CI=45-77%) of centers provided clipping of intracranial aneurysms whilst only 22% (CI=9-36%) of centers could perform the endovascular treatment. 64% (CI=48-80%) of centers did not have an endovascular specialist. Conclusion: This survey highlights health inequity in access to endovascular treatment for aSAH. Lack of diagnostic tools to identify an aneurysm and a shortfall of qualified endovascular specialists are prime reasons for this. Our findings can inform health system strengthening policies including the acquisition of equipment and capacity building in Africa.